Analisis Penggunaan Media Pembelajaran dan Motivasi Belajar Terhadap Prestasi Belajar di SMP Negeri 2 Gorontalo - I Kadek Satria Arsana; Andi Y Katili; Sulasmi . (Universitas Muhammadiyah Ponorogo, 2020)
Learning achievement is a benchmark as a result of students' achievements during the learning process. Success in learning is inseparable from the media used as well as a strong willingness to learn. This research aims to analyze the influence of learning media usage and learning motivation on students' learning achievement. The analysis used is a quantitative approach to multiple linear regressions. Data is obtained from observations and questionnaires. The results of the analysis showed that the use of learning media and learning motivation had a positive and significant effect on learning achievement. Thus, the conclusion to achieve maximum achievement needs to be optimized the use of learning media as well as stimulate the motivation of students both motivation from within and external motivation